1997
DOI: 10.1097/00000542-199709000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Serious Complications Related to Regional Anesthesia

Abstract: (1) The incidence of cardiac arrest and neurologic injury related to regional anesthesia were very low, but both were more than three SDs greater after spinal anesthesia than after other regional procedures. (2) Two thirds of the patients with neurologic deficits had either a paresthesia during needle placement or pain on injection. (3) Seventy-five percent of the neurologic deficits after nontraumatic spinal anesthesia occurred in patients who had received hyperbaric lidocaine, 5%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
333
3
27

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,020 publications
(371 citation statements)
references
References 14 publications
8
333
3
27
Order By: Relevance
“…SA-related complications range from insignificant to life threatening. A large survey in France revealed that the incidence of serious spinal (and epidural) complications were relatively low (2). In this survey, among 40640 performed procedures, the most frequent serious complication was cardiac arrest (n=26), followed by radiculopathy (n=19), death (n=6) and cauda equina syndrome (n=5).…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…SA-related complications range from insignificant to life threatening. A large survey in France revealed that the incidence of serious spinal (and epidural) complications were relatively low (2). In this survey, among 40640 performed procedures, the most frequent serious complication was cardiac arrest (n=26), followed by radiculopathy (n=19), death (n=6) and cauda equina syndrome (n=5).…”
Section: Introductionmentioning
confidence: 82%
“…The incidence of neurological complications after neuraxial anaesthesia is not perfectly clear (0-0.08%) (2,4). Furthermore, spinal cord (SC) ischaemia is a rare event when compared to cerebral ischaemia.…”
Section: Introductionmentioning
confidence: 99%
“…A debilidade e defeitos sensoriais podem ser duradouros. 4 Recomendamos um breve exame neurológico dos membros inferiores antes de um protocolo de raquianestesia e, em uma situação de queda do pé relacionada à raquianestesia, um diagnóstico urgente é necessário e um processo de tratamento é fundamental para melhores resultados em longo prazo.…”
Section: Revistaunclassified
“…ultrasound imaging technology is expensive, subjective and operator-dependent 17 39 44 45. The incidence of permanent neurological damage after peripheral nerve block, a most feared complication of regional anaesthesia, has been quoted to be in the order of 1 : 5000–1 : 10 000 46 47. So, to show a significant difference in terms of nerve safety of ultrasound-guided nerve blocks, a very large study would be required 48…”
Section: Review Of Literaturementioning
confidence: 99%